CORPORATE RESPONSIBILITY AT CHEVRON (Utah Environmental Law Review; Vol 31 No 1 (2011), 2011)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} Chevron is very grateful to the University of Utah for giving us the opportunity to address why it is important for companies to play a role in helping build a more sustainable society. One of the best examples of partnerships for sustainability, which I will discuss later, lies right here on campus. We were asked to address three questions: 1.      Why is it important, or necessary, for corporations to play a role in helping build a more sustainable society? 2.      In what ways does promoting sustainability and sustainable practices fit, or not fit, with your company's objectives? Do you see sustainability as furthering, or cutting against, shareholder returns / profits, and why? 3.      Can you give specific examples of how your company has strived to become more sustainable?